Pengaruh Perkembangan Kognitif Terhadap Berfikir Kritis Siswa Pada Mata Pelajaran PAI Di SDN Pelita Jaya Kota Sukabumi - Rubi Babullah; Mulyawan Safwandy Nugraha (PT. ALHAFI BERKAH INDONESIA, 2023)
This research was conducted with the aim of knowing how much influence cognitive development has on students' critical thinking in PAI subjects in elementary schools. This study uses a quantitative approach with a correlational type with the aim of knowing the relationship between each variable. Involved 35 samples taken from grade 4-6 students at SDN Pelita Jaya by distributing questionnaires using a Likert scale and making observations. In the initial findings it was revealed that there were some students who tended not to be able to maximize the level of their critical thinking power caused by inappropriate cognitive development. The results of this study indicate that the data normality test for variables X and Y using the Kolmogorov-Smirnov is fairly normal. With the results of the linear regression test showing that Y = 27,722 + 0.612X with a value of Fcount > Ftable, namely 27,289 > 4.14, the regression model is linear. While the R2 value is 0.453 which indicates that cognitive development affects students' critical thinking by 45.3% which can be categorized as rather low. Then the tcount > ttable with a significance level of 0.05%, namely 5,224 > 2,034 which shows that there is a correlation that is strong enough to make H0 rejected and Ha accepted.